Optimization of Growth and Yield of Eggplant (Solanum melongena L.) Through the Application of Cow Manure and Eco Enzyme - Yunidawati, Wiwik (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The aim of this study was to determine the effect of cow manure and eco enzyme application on the growth and yield of eggplant (Solanum melongena L.), as well as their interaction. This study used a Factorial Randomized Block Design (RBD) consisting of two factors. The first factor was cow manure application, divided into three levels: K0 = control (no treatment), K1 = 2 kg/plot, and K2 = 4 kg/plot. The second factor was eco enzyme application, divided into three levels: E0 = control (no treatment), E1 = 400 ml/plant, and E2 = 800 ml/plant. The observed parameters included number of leaves (leaves), plant height (cm), number of flowers (buds), number of fruits per sample (fruits), number of fruits per plot (fruits), fruit weight per sample (grams), and fruit weight per plot (grams). Statistical analysis showed that the application of cow manure had no significant effect on flowering time, but had a significant and highly significant effect on number of leaves, plant height, number of fruits per sample, number of fruits per plot, fruit weight per sample, and fruit weight per plot. The best treatment was K2 (4 kg/plot). Statistical analysis also indicated that eco enzyme application had no significant effect on number of leaves, plant height, and flowering time, but had a highly significant effect on number of fruits per sample, number of fruits per plot, fruit weight per sample (grams), and fruit weight per plot (grams). The interaction between cow manure and eco enzyme application showed no significant effect on number of leaves (leaves), plant height (cm), flowering time (days), number of fruits per plot (fruits), and fruit weight per sample (grams), but had a significant effect on number of fruits per sample (fruits) and fruit weight per plot (grams).